Risk and protective factors for posttraumatic stress disorder in trauma-exposed individuals during the COVID-19 pandemic – findings from a pan-European study. Issue 2 (19th December 2022) - Lotzin, Annett; Krause, Linda; Acquarini, Elena; Ajdukovic, Dean; Anastassiou-Hadjicharalambous, Xenia; Ardino, Vittoria; Bondjers, Kristina; Böttche, Maria; Dragan, Małgorzata; Figueiredo-Braga, Margarida; Gelezelyte, Odeta; Grajewski, Piotr; et al.
ABSTRACT: Background: The COVID-19 pandemic is a health emergency resulting in multiple stressors that may be related to posttraumatic stress disorder (PTSD). Objective: This study examined relationships between risk and protective factors, pandemic-related stressors, and PTSD during the COVID-19 pandemic. Methods: Data from the European Society of Traumatic Stress Studies (ESTSS) ADJUST Study were used. N  = 4, 607 trauma-exposed participants aged 18 years and above were recruited from the general populations of eleven countries (Austria, Croatia, Georgia, Germany, Greece, Italy, Lithuania, the Netherlands, Poland, Portugal, and Sweden) from June to November 2020. We assessed sociodemographic (e.g. gender), pandemic-related (e.g. news consumption), and health-related (e.g. general health condition) risk and protective factors, pandemic-related stressors (e.g. fear of infection), and probable PTSD (PC-PTSD-5). The relationships between these variables were examined using logistic regression on multiple imputed data sets. Results: The prevalence of probable PTSD was 17.7%. Factors associated with an increased risk for PTSD were younger age, female gender, more than 3 h of daily pandemic-related news consumption (vs. no consumption), a satisfactory, poor, or very poor health condition (vs. a very good condition), a current or previous diagnosis of a mental disorder, and trauma exposure during the COVID-19 pandemic. Factors associated with a reduced risk for PTSD included a medium and high income (vs. very low income), face-to-face contact less than once a week or 3–7 times a week (vs. no contact), and digital social contact less than once a week or 1–7 days a week (vs. no contact). Pandemic-related stressors associated with an increased risk for PTSD included governmental crisis management and communication, restricted resources, restricted social contact, and difficult housing conditions. Conclusion: We identified risk and protective factors as well as stressors that may help identify trauma-exposed individuals at risk for PTSD, enabling more efficient and rapid access to care. HIGHLIGHTS: N  =  4, 607 trauma-exposed adult participants were recruited from the general population during the first year of the COVID-19 pandemic. The prevalence for probable posttraumatic stress disorder was 17.7%. We identified risk factors (e.g. poor health condition) and protective factors (e.g. social contact) associated with posttraumatic stress disorder.